(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: In this study, we investigated the potential immune-enhancing effects in addition to anti-oxidative stress properties of commercially accessible Bacillus subtilis supplementation in Barki lambs. Materials and Methods: Twenty apparently healthy weaned Barki lambs were used in this study and distributed randomly into two experimental groups: Negative control group, received control basal diet without any feed supplements and a supplemented group, received control basal diet supplemented with water added to commercially accessible bacilli at 1 gm/l/day for 30 consecutive days. Blood samples were collected from each lamb before starting the experiment (T0), 2 weeks (T15), and 4 weeks (T30) post-supplementation for serum biochemical analyses, total leucocytes and lymphocytes count, and real-time polymerase chain reaction assays. Results: The supplemented group showed a significant increase (p < 0.05) in the total number of leukocytes and the number of lymphocytes, lysozyme activity, reduced glutathione, total antioxidant capacity with a significantly lower malondialdehyde values at T30 and significantly higher levels (p < 0.05) of serum catalase and nitric oxide at T15 as compared with control ones. B. subtilis elicited maximal up-regulation of most of the studied genes compared with the control group. Conclusion: The results herein suggest that B. subtilis could be used as useful nutritional supplements to support the immune system in healthy lambs. J. Adv. Vet. Anim. Res., 6(3): 333-340, September 2019